Analisis Kepatuhan Prinsip Syariah dalam Layanan E-Money Perspektif Maqashid Syariah - Qaidul Muttaqin; Umrotul Khasanah (Jurnal Ilmiah Ekonomi Islam, 2023)
Electronic money is basically the same as ordinary money because it functions as a means of payment for goods buying and selling transactions. From a Sharia perspective, electronic money law is halal. Sharia principles must be considered in the development of e-money services because these principles are based on fundamental Islamic values. The method used in this research is a qualitative method with the type of literature review. From the research result, e-money circulating in Indonesia, in accordance with Sharia principles and can be used if it follows and is in accordance with the requirements in the DSN-MUI fatwa, and the implementation of Sharia machair in e-money can be realized if it provides good benefits to users and organizers.